Titanium pigment in tissues of drug addicts: report of 5 necropsied cases - Lima, Marcus Aurelho de; Santos, Vitorino Modesto dos; Demachki, Samia; Lazo, Javier (Revista do Hospital das Clínicas, 2004)
The aim of this report is to describe the anatomic-pathologic findings from necropsies of 5 drug addicts with titanium pigment in several organs after chronic intravenous injection of crushed propoxyphene hydrochloride tablets. Samples from liver, spleen, lungs, lymph nodes, and bone marrow were obtained, and after being grossly studied, they were submitted to evaluation using common light and polarized microscopy. In all 5 cases, a pigment with characteristics of titanium dioxide was found within tissue samples of the organs studied. Our findings suggest that research concerning titanium pigment within body tissues should be enhanced, considering the potential contribution of this morphologic data to forensic pathology.